2018
DOI: 10.1177/0734371x18794254
|View full text |Cite
|
Sign up to set email alerts
|

Glass Ceiling in Federal Law Enforcement: An Exploratory Analysis of the Factors Contributing to Women’s Career Advancement

Abstract: In recent years, there has been limited focus on representative bureaucracy at the upper levels of government organizations. Scholarship on the glass ceiling has emphasized systematic and sociopsychological barriers as impediments for women to advance into upper level management positions. Despite the importance of continuing to highlight these obstacles, factors contributing to their success have received little attention in public administration. This study provides a descriptive analysis of the factors cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 57 publications
(70 reference statements)
0
18
0
11
Order By: Relevance
“…For example, in Yu’s (2018) exploratory study on the second generation of female leaders in federal law enforcement, 62.5% of the senior women in her study reported having a mentor and specifically identified mentorship as one of several key factors that contributed to their promotion to GS-15 and/or selection to SES. In terms of the importance of mentors, Yu (2018, p. 13) concludes “the significance of mentors and having a sponsor to advocate on [one’s] behalf ‘behind closed doors’ cannot be overemphasized.” In addition, “women, more clearly than men, usually identify a crucial figure in their career development” (Fox & Schumann, 2001, p. 383) because these individuals (i.e., mentors) “raise confidence and belief in their abilities” (White, Cox, & Cooper, 1992, p. 221). Therefore, mentorship is an essential element in women’s upward mobility and psychological support.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, in Yu’s (2018) exploratory study on the second generation of female leaders in federal law enforcement, 62.5% of the senior women in her study reported having a mentor and specifically identified mentorship as one of several key factors that contributed to their promotion to GS-15 and/or selection to SES. In terms of the importance of mentors, Yu (2018, p. 13) concludes “the significance of mentors and having a sponsor to advocate on [one’s] behalf ‘behind closed doors’ cannot be overemphasized.” In addition, “women, more clearly than men, usually identify a crucial figure in their career development” (Fox & Schumann, 2001, p. 383) because these individuals (i.e., mentors) “raise confidence and belief in their abilities” (White, Cox, & Cooper, 1992, p. 221). Therefore, mentorship is an essential element in women’s upward mobility and psychological support.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…While the figures herald a steady increase of women in senior management positions, women are still underrepresented in these leadership roles. In addition, although there is no readily available data that recognize the proportion of female managers in federal law enforcement, the figures are probably low as women encompass only 15.5% of all federal law enforcement officers to begin with (Reaves, 2012; Yu, 2018). To illustrate, in Yu’s (2015) exploratory study of the challenges women face in federal law enforcement, more than half (59.1%) the women in her study reported a lack of high-ranking female role models at their current agency.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations